An interview-informed synthesized contingency analysis to inform the treatment of challenging behavior in a young child with autism. (3rd April 2018) - Herman, Ciara; Healy, Olive; Lydon, Sinéad
ABSTRACT: Purpose: Experimental Functional analysis (EFA) is considered the "gold standard" of behavioural assessment and its use is predictive of treatment success. However, EFA has a number of limitations including its lengthy nature, the high level of expertise required, and the reinforcement of challenging behaviour. This study aimed to further validate a novel interview-informed synthesised contingency analysis (IISCA). Methods: An open-ended interview and brief direct observation informed an IISCA for a young boy with autism who engaged in challenging behaviour. Resulting data supported the hypothesis that the target behaviour was multiply controlled by escape from demands and access to tangible items. An intervention comprised of most-to-least prompting, escape extinction, differential reinforcement and a high-probability instruction sequence was evaluated using a reversal design. Results: This intervention reduced challenging behaviour to low levels and resulted in increased compliance. Conclusions : Findings support the status of the IISCA as a valid, practical, and effective process for designing function-based interventions.